Aplikasi e-Ngladog sebagai Media Informasi Wisata Kota Tangerang Selatan Berbasis Teknologi Mobile - Dicky Muhammad; Benfano Soewito (Universitas Islam Sumatera Utara, 2020)
Tangerang Selatan city or known as Tangsel is a city that located within area of Banten province which borders with DKI Jakarta province. This condition makes Tangsel city becomes economic support for citizen of DKI Jakarta which is proved by the presence of many hotel, housing and shopping center in Tangsel. The existence of tourism in Tangsel is various, however promotion effort for the tourism in this city is considered lower compared to its surrounding cities. On the official website of Tangsel tourism office, detailed data of tourism can’t be found yet. In order to support the tourism promotion so in this research an application was designed and created as information media of Tangsel city tourism based on mobile technology. This application called as e-Ngladog which was created by using Android Studio software with stored database in web server. This application’s function is to show various tourisms in Tangsel such as nature, artificial, historical and cultural, culinary, shopping and hotel tourisms, and it can be ran on android device that connected to the internet. This application also can be linked with google maps which has already been installed on smartphone device to show route to the location of certain tourism. Based on test that had been done with Black Box Testing method, it can be known that features on the application can perform in accordance with their design program.